Analysis of Transport Layer Security and Secure Socket Layer protocols as security and competitiveness mechanisms in digital organizations (Technological Innovations Journal, 2024)
The growth and competitiveness of organizations largely depend on digitalization, which poses new challenges in cybersecurity. This article aims to identify the importance of SSL and TLS protocols in key sectors of the organizational environment. A qualitative approach was followed, using a systematic review under the PRISMA methodology. A search was conducted in the Google Scholar, Dialnet, and La Referencia databases, using the descriptors "protocol, SSL, security, TSL, cybersecurity" in both English and Spanish. Articles and thesis papers published between 2014 and 2024 were considered, and 14 works were selected for the final review. The review showed that both protocols ensure the confidentiality, integrity, and authentication of communications in systems and applications, mainly preventing attacks such as phishing, man-in-the-middle, data dictionary, and interruptions with legitimate websites. In conclusion, protocols are the first step in security measures for web infrastructure in a fluctuating and highly competitive digital environment, with influence in sectors such as finance, e-commerce, services, and even digital government. It is important that every organization establishes measures, areas, departments, and resources for its own web security to ensure reliability, prestige, and to keep business and user/customer data secure.
Keywords: cyber commerce; cyber government; cybernetics; data protection